Graph Algorithms (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This is a Reprint of one of the first Special Issues of Algorithms ever published. It focuses on the theoretical and practical performance of algorithms for solving computational problems involving graphs. Several highly cited articles are included, which investigate topics such as the maximum clique problem, the Dubins traveling salesman problem, and computing the eccentricity distribution of a graph.